2015
DOI: 10.1080/13549839.2015.1075480
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the spaces and politics of energy poverty: path-dependencies, deprivation and fuel switching in post-communist Hungary

Abstract: This paper focuses on the embeddedness of energy poverty -understood as the inability to secure a socially and materially necessitated level of energy services in the home -in the socio-technical legacies inherited from past development trajectories, as well as broader economic and institutional landscapes. Using Hungary as an example, we explore the recent expansion of energy poverty across different demographic and income groups. While much of the mainstream literature focuses on cases where energy poverty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 57 publications
1
52
0
5
Order By: Relevance
“…In Bouzarovski et al (2016) we found that energy burdens have been on the rise particularly rapidly in Hungary: from 11.6 per cent in 2005 to 16.9 per cent in 2011. While the figures for Hungary point to the pervasive presence of energy poverty across the country, neighbouring Poland and Czechia also face difficult circumstances in this regard-in light of the fact that the literature on the subject considers energy burdens near or at 10 per cent as a sign of hardship (Boardman, 1991;Fankhauser & Tepic, 2007), it is notable that significant numbers of households in all three countries have energy burdens above 20 per cent.…”
Section: Geographic Patterns Of Energy Poverty In Europementioning
confidence: 96%
See 1 more Smart Citation
“…In Bouzarovski et al (2016) we found that energy burdens have been on the rise particularly rapidly in Hungary: from 11.6 per cent in 2005 to 16.9 per cent in 2011. While the figures for Hungary point to the pervasive presence of energy poverty across the country, neighbouring Poland and Czechia also face difficult circumstances in this regard-in light of the fact that the literature on the subject considers energy burdens near or at 10 per cent as a sign of hardship (Boardman, 1991;Fankhauser & Tepic, 2007), it is notable that significant numbers of households in all three countries have energy burdens above 20 per cent.…”
Section: Geographic Patterns Of Energy Poverty In Europementioning
confidence: 96%
“…As we argued in a recent co-authored paper (Bouzarovski, Tirado Herrero, Petrova, & Ürge-Vorsatz, 2016), successive Hungarian governments have been making various attempts to buffer the impact of growing energy prices on the purchasing power of Hungarian households and voters. These politically motivated policy interventions have mainly taken the form of regulated energy prices and relatively short-lived subsidy schemes.…”
Section: Energy Poverty In Continental Europementioning
confidence: 99%
“…In a consequent study applied on the Hungarian energy sector, Bouzarovski argues that households may purposely choose to delay the payment of expensive energy bills in order not to run out of money in the winter months, thus transferring the financial consequences of energy poverty to the utility providers (Bouzarovski et al, 2015).…”
Section: Contemporary Literature Published In the Main Scientific Infmentioning
confidence: 99%
“…Domestic energy deprivation does not bring about a passive and reactive set of behaviours and practices within households and institutions (Bouzarovski, Tirado Herrero, Petrova, & Ürge-Vorsatz, 2016). Rather, the diverse strategies that are articulated with respect to the condition have far-reaching effects on the systemic conditions that underpin the emergence of energy poverty.…”
Section: Introductionmentioning
confidence: 99%
“…However, high or increasing levels of domestic energy deprivation complicate the application of policies that promote energy vulnerability-enhancing measures, such as renewable feed-in tariffs or surcharges paid by domestic energy users irrespective of income, needs or living conditions. In a number of European countries, the expansion of energy poverty among the general population has been accompanied by the adoption of household strategies orientated towards carbon-intensive and polluting fuels, such as coal or firewood (Bouzarovski et al, 2016).…”
Section: Introductionmentioning
confidence: 99%